Cover Feature: Selective Anodic Oxidation of Solketal as Acetal‐Protected Glycerol over Nickel Boride in Alkaline Media to Glyceric Acid (ChemElectroChem 4/2022). Issue 4 (11th January 2022) - Cychy, Steffen; Lechler, Sebastian; Muhler, Martin
Abstract : The Cover Feature shows the anodic oxidation of solketal, an acetal‐protected glycerol derivative, to solketalate. Subsequent acidic deprotection releases glyceric acid in high selectivity preserving the carbon chain, whereas direct glycerol oxidation over nickel boride would yield formate as main product. More information can be found in the Communication by S. Cychy, S. Lechler and M. Muhler .